The neoconservative threat to the sexual rights of children and adolescents - Mendonça, Valeria Nepomuceno Teles de; Lima, Mirella Cavalcante Vilar (Argumentum, 2023)
The article discusses the relationship between the recognition of the sexual and reproductive rights of children and adolescents and the confronting of sexual violence, aiming to demonstrate that one impact of neoconservatism on social policies in Brazil has been to leave boys and girls more exposed to this form of violence. A survey of the Catalogue of Theses and Dissertations for the Coordination of the Improvement of Higher Education Personnel (Capes), and a bibliographic review of works on the subject and of documents on international and national legal regulations was undertaken. This indicates that sexual and reproductive rights form a broad field within the human rights of women, children and adolescents in international treaties and conventions to which Brazil is a signatory. Under the Bolsonaro Government, the propagation of conservative values and the fight against a supposed gender ideology represented an obstacle to the recognition of the sexual rights of children and adolescents and the reproductive rights of adolescents, and went in the opposite direction to the full protection advocated by the Statute of the Child and Adolescent.Keywords: Child and adolescent; Sexual and reproductive rights; Neoconservatism.